Physiological responses of beet plants irrigated with saline water and silicon application - Melo Filho, José Sebastião de; Silva, Toshik Iarley da; Gonçalves, Anderson Carlos de Melo; Sousa, Leonardo Vieira de; Véras, Mario Leno Martins; Dias, Thiago Jardelino (Comunicata Scientiae, 2020)
Although not considered an essential element, silicon can be used to increase crop productivity, especially under stress conditions. In this sense, the objective was to evaluate the gas exchange of beet plants irrigated with saline water depending on the application of silicon. The experiment was conducted in a randomized block design, in a 5 x 5 factorial, referring to five levels of electrical conductivity of irrigation water (ECw): (0.5; 1.3; 3.25; 5.2 and 6.0 dS m-1) and five doses of silicon (0.00; 2.64; 9.08; 15.52 and 18.16 mL L-1), with six beet plants as an experimental unit. The effect of treatments on beet culture was evaluated at 30 and 60 days after irrigation with saline water from measurements of internal carbon concentration, stomatal conductance, net photosynthesis rate, instantaneous water use efficiency and instantaneous carboxylation efficiency using the LCpro+Sistem infrared gas analyzer (IRGA). Irrigation with saline water reduced the gas exchange of beet plants at 60 days after irrigation, but at 30 days after irrigation, the use of saline water increased stomatal conductance, transpiration rate and internal carbon concentration. The application of silicon decreased stomatal conductance, internal carbon concentration and efficiency in the use of water, but increased the rate of net photosynthesis, the rate of transpiration and instantaneous efficiency of carboxylation at 30 and 60 days after irrigation.